INFORMATION AND PSYCHOLOGICAL INFLUENCE AS A MEETING OF PROFESSIONAL ACTIVITY OF MILITARY SERVICES (Psychology Travelogs, 2023)
The study of the motivational sphere of servicemen made it possible to draw the following conclusions: the system of motivation is an important part of the professional activity of servicemen; motivational theories are a valuable source for military leaders in the field of formation of an effective mechanism of positive motivation of professional activities of servicemen; the ways of managerial influence on the activation of military personnel are different, but their focus on achieving the goals is one; the creation of an effective motivational system of servicemen significantly increases the significance of their military service and provides the possibility of their professional growth, the manifestation of their professional abilities.Research on the characteristics of military motivation has shown that the effectiveness of military service is determined not only by goals, certain guidelines or qualitatively developed solutions and justified actions for their implementation, but largely depends on the military, their professionalism and their motivation to work as best they can.Beliefs focused on their own critical perception of reality use certain exposure algorithms. These algorithms include the availability of the logic of beliefs for the intelligence of the object of influence, the use of facts, known objects, generalizing proposals in belief, logically unrelated theses and emotionally colored facts.The military is most inclined in its activities to «Service», ie they try to protect and defend Ukraine from the enemy as best they can. Researchers also appreciate the public importance, respect, material reward associated with the position, the prestige of the profession, and the ability to make social changes. Although the leading motive for choosing a profession for many servicemen is the ability to change their careers, most of the subjects are not sufficiently satisfied with their professional activities. This can be explained by the dissonance of the expected and obtained results.
Keywords: motive; motivation; career orientations; value priorities; professional activity; servicemen; information and psychological impact